A porous carbon material based on circuit board waste and a preparation method and application thereof

CN121872383BActive Publication Date: 2026-10-09ZHONGNENG (TIANJIN) ENVIRONMENTAL PROTECTION RENEWABLE RESOURCES UTILIZATION CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610087485.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-22
Publication Date
2026-10-09
Estimated Expiration
2046-01-22

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供一种基于电路板废料的多孔碳材料及其制备方法和应用,多孔炭材料具有高比表面积和孔体积,提高潮湿环境下对四氯化碳的吸附率,解决传统活性炭抗湿性能差的问题

Benefits of technology

本发明采用氟化钾、氟化钠复合活化体系,替代传统氢氧化钾、氯化钾,其一,氟离子可与原料中残留的硅氧化物(玻璃纤维)发生反应,生成氟硅酸盐,破坏硅氧键的稳定结构,促进硅氧化物的分解与去除,避免其堵塞孔隙;其二,氟化物在高温下分解产生的活性物种可与碳基质发生反应,刻蚀形成丰富的微孔与介孔结构,大幅提升比表面积与孔体积;其三,氟化钾与氟化钠的协同作用可调节孔径分布,增加介孔占比,减少水汽在微孔中的强吸附作用,实现了孔结构调控与抗湿性能提升的双重目标,所制备的多孔碳材料在高湿度环境下仍保持优异的四氯化碳吸附性能,适用于多种潮湿工况的VOCs治理,应用范围广泛。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121872383B_ABST
    Figure CN121872383B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of activated carbon preparation, and specifically discloses a porous carbon material based on circuit board waste, a preparation method and application thereof, and the preparation method comprises the following steps: S1, raw material pretreatment; S2, mixed activation with a composite activating agent; S3, carbonization treatment; S4, doping modification: heat treatment with ammonium fluoride, and then soaking treatment in a methyl triethoxysilane ethanol solution; and S5, acid pickling purification with a composite acid pickling solution to obtain a moisture-resistant porous carbon material.The porous carbon material based on circuit board waste and the preparation method and application thereof have high specific surface area and pore volume, improve the adsorption rate of carbon tetrachloride in a humid environment, solve the problem of poor moisture resistance of traditional activated carbon, realize the resource utilization of non-metallic waste of waste circuit boards, and have the dual advantages of environmental protection and performance, and are more suitable for industrial VOCs treatment scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of activated carbon preparation technology, and in particular to a porous carbon material based on circuit board waste, its preparation method, and its application. Background Technology

[0002] Waste printed circuit boards (WPCBs) are core components of electronic devices and constitute a significant portion of electronic waste in today's society. While metal particles are efficiently recycled after dismantling and sorting, research on the resource utilization of non-metallic powders has progressed slowly. Non-metallic powders typically consist of resin (40%), glass fiber (58%), and a very small amount of unseparated metal. Epoxy resin, rich in carbon and various organic components, holds promise as another raw material for activated carbon production, turning waste into treasure. Utilizing waste resin to produce activated carbon can reduce over-reliance on natural resources and lower the cost of raw materials. Furthermore, it can create a closed-loop resource recycling system, powerfully promoting sustainable development and contributing to the coordinated development of the economy and the environment.

[0003] In the prior art, there are already solutions for reusing the waste epoxy resin powder after metal recycling processes on waste circuit boards. Chinese invention patent application CN102923702A discloses a method for preparing activated carbon from waste printed circuit boards. Using the non-metallic portion of the waste printed circuit boards after metal removal as raw material, and KOH, NaOH, K2CO3, or Na2CO3 as activating agents, it employs either a one-step carbon activation method or a step-by-step carbon activation method to prepare activated carbon with excellent adsorption performance. The methylene blue adsorption capacity reaches 240 mg / g, and the adsorption performance of the product meets the requirements of commercially available activated carbon. However, with the improvement of national standards for activated carbon, the adsorption performance of activated carbon still needs further improvement. Furthermore, the presence of silicon increases the mass of activated carbon and limits the improvement of its surface area. The pore structure characteristics, surface chemical properties, and residual impurities of activated carbon together lead to adsorption competition between water molecules and volatile organic compounds (VOCs). In humid environments, water vapor easily occupies adsorption sites, resulting in a significant decrease in the adsorption performance of VOCs, making it difficult to meet the usage requirements of high humidity conditions (such as rainy seasons, coastal areas, and high-humidity industrial workshops). Summary of the Invention

[0004] The purpose of this invention is to provide a porous carbon material based on circuit board waste, its preparation method and application. The porous carbon material has a high specific surface area and pore volume, which improves the adsorption rate of carbon tetrachloride in humid environments and solves the problem of poor moisture resistance of traditional activated carbon.

[0005] To achieve the above objectives, the present invention provides a method for preparing porous carbon materials based on circuit board waste, comprising the following steps: S1. Raw material pretreatment: The non-metallic powder of waste circuit boards is placed in an air environment for pre-carbonization. After cooling, it is ground, sieved and subjected to gravity vibration to obtain pre-carbonized material. S2. Mixed activation: The pre-carbonized material obtained in S1 is mixed with the composite activator according to the mass ratio, deionized water is added, the mixture is stirred evenly and then dried to obtain a solid mixture. S3, carbonization treatment: The solid mixture obtained in S2 is transferred to an atmosphere tube furnace, and carbonization treatment is carried out under nitrogen protection. After cooling, black solid powder is obtained. S4. Doping modification: The black solid powder obtained in S3 is mixed with ammonium fluoride according to the mass ratio and placed in an atmosphere tube furnace. It is then heat-treated under nitrogen protection. After cooling, it is ground and sieved. Then it is soaked in methyltriethoxysilane ethanol solution, filtered and dried to obtain a porous carbon matrix. S5. Acid washing and purification: Mix the composite acid washing solution with the porous carbon matrix obtained in S4, stir and acid wash, let stand and pour off the supernatant, then wash with ultrapure water until neutral, filter and dry to obtain moisture-resistant porous carbon material.

[0006] Preferably, in S1, the pre-carbonization temperature is 220~240℃ and the time is 6~8h.

[0007] Preferably, in S2, the mass ratio of the pre-carbonized material to the composite activator is 1:3~4, and the composite activator is specifically a mixture of potassium fluoride and sodium fluoride, with the mass ratio of potassium fluoride to sodium fluoride being 1~3:1.

[0008] Preferably, in S2, after adding deionized water and stirring evenly, the process of drying is as follows: After adding deionized water, stir at a stirring speed of 300~800r / min for 2~4h, and dry at 60~100℃.

[0009] Preferably, in S3, the carbonization process specifically includes: Under a nitrogen flow rate of 0.3~0.5 L / min, the temperature is first increased to 350℃ at 10℃ / min, and then increased to 780~820℃ at 5℃ / min, and held for 2~4 hours.

[0010] Preferably, in step S4, the ratio of the black solid powder, the ammonium fluoride, and the methyltriethoxysilane ethanol solution is 10g:1g:100mL, and the mass fraction of the methyltriethoxysilane ethanol solution is 0.6~1.0%.

[0011] Preferably, in S4, the heat treatment specifically includes: The heat treatment temperature is 340~360℃, and the heating time is 1~2h.

[0012] Preferably, in S5, the composite acid solution is specifically a mixture of hydrochloric acid and oxalic acid with a total concentration of 3.5~4.5 mol / L, and the volume ratio of hydrochloric acid to oxalic acid is 2~3:1.

[0013] Preferably, S5 is as follows: The composite acid washing solution was mixed with the porous carbon matrix at a stirring speed of 420~630r / min for 6~10h. After standing, the supernatant was discarded. Then, it was repeatedly washed with ultrapure water until neutral. The mixture was filtered using a Buchner funnel and medium-speed filter paper. The filter cake was dried at 50~90℃ to obtain a moisture-resistant porous carbon material.

[0014] The present invention also provides a porous carbon material based on circuit board waste.

[0015] This invention also provides an application of porous carbon materials based on circuit board waste in the adsorption of carbon tetrachloride gas in a humid environment.

[0016] Therefore, the present invention employs the above-mentioned porous carbon material based on circuit board waste, its preparation method, and its application, with the following beneficial effects: This invention employs a potassium fluoride and sodium fluoride composite activation system to replace traditional potassium hydroxide and potassium chloride. Firstly, fluoride ions react with residual silicon oxides (glass fibers) in the raw materials to form fluorosilicates, disrupting the stable structure of silicon-oxygen bonds, promoting the decomposition and removal of silicon oxides, and preventing them from clogging pores. Secondly, the active species generated by the decomposition of fluorides at high temperatures react with the carbon matrix, etching to form abundant micropores and mesopores, significantly increasing the specific surface area and pore volume. Thirdly, the synergistic effect of potassium fluoride and sodium fluoride can regulate pore size distribution, increase the proportion of mesopores, and reduce the strong adsorption of water vapor in micropores, achieving the dual goals of pore structure regulation and improved moisture resistance. The prepared porous carbon material maintains excellent carbon tetrachloride adsorption performance even in high humidity environments, making it suitable for VOCs treatment under various humid conditions and with a wide range of applications.

[0017] The unpurified black solid powder after carbonization of this invention has a large amount of activator decomposition products (such as potassium salts), molten silicon oxide products and a small amount of metal impurities remaining on its surface. This causes a large number of defect sites and active groups to form on the surface of the carbon material. Chemical modification (silane grafting, fluoride doping) can directly react with these active sites. Some modifiers (such as fluorides) can further etch the pores, clear the blocked micropores and increase the proportion of mesopores. The subsequent purification steps simultaneously remove the modification by-products and original impurities. The modified layer grafted on the carbon surface can play a protective role, reduce the erosion of the pore walls by the acid solution during the pickling process, and improve the retention rate of specific surface area and pore volume.

[0018] The raw materials of this invention are derived from non-metallic waste materials of waste circuit boards, which are inexpensive and realize the resource utilization of waste. The preparation process does not use or generate any toxic or harmful substances. The waste acid treatment is simple. Hydrochloric acid can efficiently remove residual metal impurities (such as iron, copper, etc.) and some inorganic acid salts from carbonization products. Oxalic acid, as a weak acid, has a chelating effect and can form soluble complexes with residual silicon, aluminum and other elements to achieve deep impurity removal, taking into account both impurity removal efficiency and environmental safety.

[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0020] Figure 1 This is the 120-minute saturated adsorption result of a porous carbon material based on circuit board waste, its preparation method, and its application examples according to the present invention. Figure 2 The present invention provides a porous carbon material based on circuit board waste, its preparation method, and application examples. The adsorption rate over time curves are shown under different humidity conditions. (a) is the adsorption rate over time curve under low humidity conditions, (b) is the adsorption rate over time curve under medium humidity conditions, and (c) is the adsorption rate over time curve under high humidity conditions. Figure 3 This is a statistical chart of the cyclic adsorption stability test of a porous carbon material based on circuit board waste, its preparation method, and its application embodiments according to the present invention. Detailed Implementation

[0021] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.

[0022] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0023] In this invention, the raw materials include: Potassium fluoride: Purity >98%, industrial grade; Sodium fluoride: Purity >98%, industrial grade; Potassium hydroxide: purity >96%; Potassium chloride: analytical grade; Hydrochloric acid: 35-38% by mass, analytical grade; Oxalic acid: Purity >99.5%, analytical grade; FR-4 type waste circuit boards: non-metallic powder after mechanical crushing and metal recycling.

[0024] Example 1 A porous carbon material based on circuit board waste is prepared by the following method: Raw material pretreatment: Take 100g of FR-4 type waste circuit board non-metallic powder, place it in an atmosphere tube furnace, pre-carbonize it at 230℃ for 7h in an air environment, cool it to room temperature, grind it with a 350W grinder, pass it through a 50-mesh sieve, and then use a 100W shaker to remove glass fiber by gravity vibration to obtain a pre-carbonized material with an ash content of less than 18%.

[0025] Mixed activation: Weigh 10g of pre-carbonized material, add 26.25g of potassium fluoride and 8.75g of sodium fluoride (mass ratio of 3:1) at a mass ratio of 1:3.5 between the pre-carbonized material and the composite activator, place them together in a beaker, add 80ml of deionized water, stir at 500r / min for 3h until the mixture is uniform, and then dry in a 90℃ oven until the moisture is completely removed to obtain a solid mixture.

[0026] Carbonization treatment: After grinding the solid mixture, it was transferred to an atmosphere tube furnace and protected with nitrogen gas at a flow rate of 0.4 L / min. The heating program was as follows: first, the temperature was increased to 350℃ at a rate of 10℃ / min, then increased to 800℃ at a rate of 5℃ / min, and held for 3 hours. After cooling to room temperature, a black solid powder was obtained.

[0027] Doping modification: Take 5g of black solid powder and mix it evenly with 0.5g of ammonium fluoride. Place it in an atmosphere tube furnace and heat treat it at 350℃ for 1.5h under nitrogen protection. After cooling, grind it through a 100-mesh sieve and then soak it in 50mL of 0.8% methyltriethoxysilane ethanol solution (stirred at 40℃ for 3h). After filtration, dry it at 110℃ for 2h to obtain a porous carbon matrix.

[0028] Acid washing and purification: A composite acid solution (hydrochloric acid to oxalic acid volume ratio 2.5:1, total concentration 4.0 mol / L) was placed in a beaker with the porous carbon matrix and stirred at 500 r / min for 8 h. After standing, the supernatant was discarded, and the mixture was repeatedly washed with ultrapure water until pH=7. The mixture was then filtered using a Buchner funnel and medium-speed filter paper. The filter cake was dried in an 80℃ drying oven to obtain a moisture-resistant porous carbon material.

[0029] Example 2 A porous carbon material based on circuit board waste is prepared in a way that differs from that in Example 1 in that the mass ratio of potassium fluoride to sodium fluoride is adjusted to 2:1.

[0030] Example 3 A porous carbon material based on circuit board waste is prepared in a way that differs from that in Example 1 in that the mass ratio of potassium fluoride to sodium fluoride is adjusted to 1:1.

[0031] Comparative Example 1 A porous carbon material based on circuit board waste is prepared in a way that differs from that in Example 1 in that potassium fluoride and sodium fluoride are replaced with potassium hydroxide and potassium chloride, and the mass ratio of potassium hydroxide to potassium chloride is 2:1.

[0032] Comparative Example 2 A porous carbon material based on circuit board waste is prepared in a way that differs from that in Example 1 in that the mass ratio of potassium fluoride to sodium fluoride is adjusted to 2:1, and the composite acid solution is replaced with a hydrochloric acid solution with a concentration of 4.0 mol / L.

[0033] Comparative Example 3 A porous carbon material based on circuit board waste differs from Example 1 in that it is not doped or modified. Its preparation method is as follows: Raw material pretreatment: Take 100g of FR-4 type waste circuit board non-metallic powder, place it in an atmosphere tube furnace, pre-carbonize it at 230℃ for 7h in an air environment, cool it to room temperature, grind it with a 350W grinder, pass it through a 50-mesh sieve, and then use a 100W shaker to remove glass fiber by gravity vibration to obtain a pre-carbonized material with an ash content of less than 18%.

[0034] Mixed activation: Weigh 10g of pre-carbonized material, add 26.25g of potassium fluoride and 8.75g of sodium fluoride (mass ratio of 3:1) at a mass ratio of 1:3.5 between the pre-carbonized material and the composite activator, place them together in a beaker, add 80ml of deionized water, stir at 500r / min for 3h until the mixture is uniform, and then dry in a 90℃ oven until the moisture is completely removed to obtain a solid mixture.

[0035] Carbonization treatment: After grinding the solid mixture, it was transferred to an atmosphere tube furnace and protected with nitrogen gas at a flow rate of 0.4 L / min. The heating program was as follows: first, the temperature was increased to 350℃ at a rate of 10℃ / min, then increased to 800℃ at a rate of 5℃ / min, and held for 3 hours. After cooling to room temperature, a black solid powder was obtained.

[0036] Doping modification: Take 5g of black solid powder and mix it evenly with 0.5g of ammonium fluoride. Place it in an atmosphere tube furnace and heat treat it at 350℃ for 1.5h under nitrogen protection. After cooling, grind it through a 100-mesh sieve and then soak it in 50mL of 0.8% methyltriethoxysilane ethanol solution (stirred at 40℃ for 3h). After filtration, dry it at 110℃ for 2h to obtain a porous carbon matrix.

[0037] Acid washing and purification: A composite acid solution (hydrochloric acid to oxalic acid volume ratio 2.5:1, total concentration 4.0 mol / L) was placed in a beaker with the porous carbon matrix and stirred at 500 r / min for 8 h. After standing, the supernatant was discarded, and the mixture was repeatedly washed with ultrapure water until pH=7. The mixture was then filtered using a Buchner funnel and medium-speed filter paper. The filter cake was dried in an 80℃ drying oven to obtain a moisture-resistant porous carbon material.

[0038] Test 1. The porous carbon materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to structural analysis. The specific surface area, total pore volume, micropore volume, mesopores, micropore ratio and average pore size are shown in Table 1.

[0039] Table 1. Specific surface area, total pore volume, micropore volume, mesopores, micropore percentage, and average pore size data.

[0040] Table 1 shows that the composite system of potassium fluoride and sodium fluoride has a significantly stronger ability to decompose silicon oxides than the traditional potassium hydroxide / potassium chloride system, reducing the blockage of pores by silicon impurities. Furthermore, fluoride ion etching more easily forms mesoporous enrichment structures. With increasing sodium fluoride content, pore-forming activity weakens, silicon oxide decomposition becomes incomplete, the proportion of micropore volume gradually increases, and the mesopore volume gradually decreases. At a potassium fluoride:sodium fluoride ratio of 3:1, the fluoride ion release efficiency is highest, resulting in the richest mesopore formation and the largest mesopore volume (0.836 cm⁻¹). 3 The fluoride-etched pores have the lowest micropore percentage (12.3%), the highest specific surface area and total pore volume, and the pore size is more uniform, demonstrating the effect of fine control of pores.

[0041] Traditional potassium hydroxide and potassium chloride treatments can only lower the melting point of silicon oxides, but cannot completely decompose them. This results in micropores dominating the pore structure, while silicon impurities clog mesopores, leading to insufficient mesopore development. Composite acid etching (hydrochloric acid + oxalic acid) can deeply remove impurities such as silicon and aluminum through the chelating effect of oxalic acid, while hydrochloric acid alone can only remove metallic impurities and cannot effectively remove silicate residues. These impurity residues significantly inhibit mesopore development. Secondary etching with ammonium fluoride can unclog micropores and enlarge mesopores, while methyltriethoxysilane modification optimizes the surface properties of the pores.

[0042] 2. The adsorption performance and stability of the porous carbon materials prepared in Example 1 and Comparative Examples 1 to 3 were tested for carbon tetrachloride gas under different humidity conditions.

[0043] Test conditions: Adsorbent dosage 0.5g, adsorption bed temperature 25℃, initial carbon tetrachloride concentration 1000ppm, gas flow rate 50mL / min, humidity conditions: low humidity (RH=30%±5%), medium humidity (RH=60%±5%), high humidity (RH=90%±5%), test time 120min, sampling and testing every 10min. Then, high humidity (RH=90%±5%), 5 adsorption-desorption cycles were performed. The saturated adsorption capacity after 120min is shown below. Figure 1 As shown in the figure, the adsorption rate over time curves under different humidity conditions are as follows: Figure 2 As shown, the cyclic adsorption stability is as follows: Figure 3 As shown in Table 2, the adsorption rate and the retention rate after 5 adsorption-desorption cycles are as follows.

[0044] Table 2 Adsorption rate and retention rate after 5 adsorption-desorption cycles

[0045] Depend on Figure 1 It can be seen that the saturated adsorption capacity of the porous carbon materials prepared in Examples 1 to 3 is significantly higher than that of Comparative Examples 1 to 3 under low, medium, and high humidity conditions, and the effect of humidity change on the adsorption capacity of the Example groups is smaller. Among them, Example 1 has the best saturated adsorption capacity, reaching 1582 mg / g, 1550 mg / g, and 1510 mg / g under low, medium, and high humidity conditions, respectively. The saturated adsorption capacity of traditional potassium hydroxide / potassium chloride activation is the lowest, only 1235 mg / g under high humidity, which is 18.2% lower than that of Example 1. The saturated adsorption capacity of single hydrochloric acid washing and unmodified materials is between that of the Example groups and Comparative Example 1, which reflects the synergistic effect of fluoride composite activation, composite washing, and doping modification on adsorption capacity.

[0046] Depend on Figure 2 It can be seen that the adsorption rate increases rapidly in the initial stage of adsorption (0~60min) and slows down in the later stage (60~120min); the higher the humidity, the more significant the difference in adsorption performance among the groups: under low humidity, the adsorption rate of Example 1 reached 96.5% after 120min, while that of Comparative Example 1 was 86.3%; under high humidity, the adsorption rate of Example 1 still remained at 93.9%, while that of Comparative Example 1 was only 75.6%, indicating that the present invention has a better anti-moisture adsorption ability, and its high mesoporous ratio and hydrophobic modification effectively weaken the competition of water vapor for adsorption sites.

[0047] Depend on Figure 3As shown in Table 2, the cyclic adsorption stability of Example 1 is significantly better than that of the comparative examples. After 5 adsorption-desorption cycles, the saturated adsorption capacity of Example 1 under high humidity conditions still reached 1412 mg / g, with a cycle retention rate of 93.5%; the cycle retention rates of Comparative Examples 1 and 3 were only 81.7% and 81.9%, respectively, and that of Comparative Example 2 was 87.0%. Comparative Example 1 exhibited the worst high-humidity adsorption rate and cycle stability due to the pore structure defects and hydrophilic surface of the traditional activation system. Comparative Example 2 suffered from impurity residue due to single acid washing, while Comparative Example 3, lacking hydrophobic modification and secondary etching, also showed poor adsorption rate and stability. This demonstrates the feasibility of using a process route combining fluoride composite activation, doping modification, and composite acid washing to improve cycle stability. By designing chemical modification between the carbonization and purification steps, the high-activity surface of the carbonization product can be utilized to enhance modification efficiency. Subsequent purification simultaneously removes original impurities and modification byproducts. The modified layer protects the pore structure and enhances moisture resistance, reducing adsorbate residue and pore blockage, extending the material's service life, and ultimately achieving a synergistic improvement in adsorption performance and stability.

[0048] Therefore, the present invention adopts the above-mentioned porous carbon material based on circuit board waste, its preparation method and application. The porous carbon material has a high specific surface area and pore volume, which improves the adsorption rate of carbon tetrachloride in humid environments and solves the problem of poor moisture resistance of traditional activated carbon.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing porous carbon materials based on circuit board waste, characterized in that, Includes the following steps: S1. Raw material pretreatment: The non-metallic powder of waste circuit boards is placed in an air environment for pre-carbonization. After cooling, it is ground, sieved and subjected to gravity vibration to obtain pre-carbonized material. S2. Mixed activation: The pre-carbonized material obtained in S1 is mixed with the composite activator according to the mass ratio, deionized water is added, the mixture is stirred evenly and then dried to obtain a solid mixture; the composite activator is specifically a mixture of potassium fluoride and sodium fluoride, and the mass ratio of potassium fluoride to sodium fluoride is 1~3:1; S3, carbonization treatment: The solid mixture obtained in S2 is transferred to an atmosphere tube furnace, and carbonization treatment is carried out under nitrogen protection. After cooling, black solid powder is obtained. S4. Doping modification: The black solid powder obtained in S3 is mixed with ammonium fluoride according to the mass ratio and placed in an atmosphere tube furnace. It is then heat-treated under nitrogen protection. After cooling, it is ground and sieved. Then it is soaked in methyltriethoxysilane ethanol solution, filtered and dried to obtain a porous carbon matrix. S5. Acid washing and purification: Mix the composite acid washing solution with the porous carbon matrix obtained in S4, stir and acid wash, let stand and pour off the supernatant, then wash with ultrapure water until neutral, filter and dry to obtain moisture-resistant porous carbon material.

2. The method for preparing porous carbon material based on circuit board waste according to claim 1, characterized in that, In S1, the pre-carbonization temperature is 220~240℃ and the time is 6~8h.

3. The method for preparing porous carbon material based on circuit board waste according to claim 1, characterized in that, In S2, the mass ratio of the pre-carbonized material to the composite activator is 1:3~4.

4. The method for preparing porous carbon material based on circuit board waste according to claim 1, characterized in that, In S3, the carbonization process specifically includes: Under a nitrogen flow rate of 0.3~0.5 L / min, the temperature is first increased to 350℃ at 10℃ / min, and then increased to 780~820℃ at 5℃ / min, and held for 2~4 hours.

5. The method for preparing porous carbon material based on circuit board waste according to claim 1, characterized in that, In S4, the ratio of the black solid powder, the ammonium fluoride, and the methyltriethoxysilane ethanol solution is 10g:1g:100mL, and the mass fraction of the methyltriethoxysilane ethanol solution is 0.6~1.0%.

6. The method for preparing porous carbon material based on circuit board waste according to claim 1, characterized in that, In S4, the heat treatment specifically includes: The heat treatment temperature is 340~360℃, and the heating time is 1~2h.

7. The method for preparing porous carbon material based on circuit board waste according to claim 1, characterized in that, In S5, the composite pickling solution is specifically a mixture of hydrochloric acid and oxalic acid with a total concentration of 3.5~4.5 mol / L, wherein the volume ratio of hydrochloric acid to oxalic acid is 2~3:

1.

8. The method for preparing porous carbon material based on circuit board waste according to claim 1, characterized in that, S5 specifically refers to: The composite acid washing solution was mixed with the porous carbon matrix at a stirring speed of 420~630r / min for 6~10h. After standing, the supernatant was discarded. Then, it was repeatedly washed with ultrapure water until neutral. The mixture was filtered using a Buchner funnel and medium-speed filter paper. The filter cake was dried at 50~90℃ to obtain a moisture-resistant porous carbon material.

9. A moisture-resistant porous carbon material prepared by the method for preparing porous carbon material based on circuit board waste as described in any one of claims 1 to 8.

10. The application of the moisture-resistant porous carbon material as described in claim 9 in the adsorption of carbon tetrachloride gas in a humid environment.

Citation Information

Patent Citations

  • Method for preparing active carbon from waste printed circuit board

    CN102923702A

  • Method for preparing porous carbon for super capacitor by waste plastic carbonization

    CN105366658A

  • Method for preparing hollow carbon adsorbent by taking paraffin oil decoloration waste soil as raw material and application

    CN112657466A